2004
DOI: 10.1080/22201009.2004.10872339
|View full text |Cite
|
Sign up to set email alerts
|

Assessing peripheral arteries in South African black women with type 2 diabetes mellitus

Abstract: Peripheral vascular disease is 2 -3 times more likely to develop in people with diabetes mellitus (DM) than in the general population.1 It can occur in 8% of people at the time of diagnosis of DM and may reach 45% by 20 years' duration. 2There are no published data on the prevalence of peripheral artery disease (PAD) or medial arterial calcification in an unselected group of black South African patients with DM. Traditionally it is thought that South African blacks have a lower incidence of vascular disease th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 12 publications
0
6
1
Order By: Relevance
“…This can be explained by the varied study diagnostic approaches of PAD with higher prevalence noted in studies using ABI measurement [7], [8], [9], [10] compared to clinical palpation of lower limb pulses [11], [12], [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This can be explained by the varied study diagnostic approaches of PAD with higher prevalence noted in studies using ABI measurement [7], [8], [9], [10] compared to clinical palpation of lower limb pulses [11], [12], [13].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Tanzania by Gulam-Abbas Z et al [9] and South Africa by Paul A et al [8] and Rheeder P [10] et al reported prevalence of 20.7%, 29.3% and 4.7% respectively. A prevalence of 52.5% was noted in the Nigerian study [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7 The article by Professor Paul Rheeder and colleagues (p. 79) takes a step toward addressing the large hiatus in knowledge of macrovascular disease in the black population of South Africa with type 2 diabetes. 8 Rheeder and co-workers (including medical students) focus on the clinical assessment of peripheral vascular disease in black women in a primary health care facility and argue that simple palpation of peripheral pulses by competent clinical examination, augmented with relatively inexpensive arterial Doppler measurements, is crucial to the evaluation of this particular macrovascular complication in this setting. Against the backdrop of increasingly expensive technology-driven methods of assessment of other vascular regions, this is refreshing and sound advice that will require dedicated translation into widespread practice at all levels of diabetes care.…”
Section: Macrovascular Disease In Type 2 Diabetes Editorialmentioning
confidence: 99%
“…In Ghana, the prevalence rate of diabetes mellitus in adults is 3.3 per cent 3 and the prevalence of PAD worldwide has been estimated at between 4.5% and 29% 4 , and in Sub Saharan Africa, the prevalence of PAD varies from 1.7-52.5% [5][6][7][8] . A study in Nigeria reported evidence of PAD in 54% of diabetic patients with foot complications 9 , whilst another study from Tanzania found PAD in 21% of diabetic patients 10 .…”
Section: Introductionmentioning
confidence: 99%